Delirium: Assessment and Management - A Review - Kumar, Nitin; Kukreti, Prerna (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2021)
Delirium is described as a syndrome characterized by disturbed consciousness, cognitive function or perception, which is acute in onset and has fluctuating course. This article serves to provide a brief review of this condition with respect to diagnostic classification, epidemiology, etiopathogenesis and types. Furthermore, a focused discussion on its assessment and management in routine clinical practice has been documented.